Analisa Rancang Bangun Aplikasi Biro Jodoh Islami Menggunakan Algoritma Profile Matching Berdasarkan Platform Android - Pramana, Ekky Bayu; Sunandar, Aris (Arcitech: Journal of Computer Science and Artificial Intelligence, 2022)
Matchmaking in the current era of globalization is also a problem faced by the younger generation. Indonesian people who are multi-ethnic and multi-religious mingle in everyday life, both in the school, college, work and home environment around us. For Muslims, getting a partner in the faith is of course the dream of every family. The problem that sometimes occurs is that parents are anxious because their child is in a relationship with someone who is not a believer or even if their child is old enough, it turns out that they still have difficulty getting a partner in the faith because of their busy schedules. This is what inspired researchers to analyze the design and build of Islamic dating agency applications using the Profile Matching Algorithm Based on the Android Platform. Through the help of this Profile Matching algorithm, it is hoped that someone can more easily find a potential partner according to the criteria he wants.